EFEKTIVITAS PENGGUNAAN PERANGKAT PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS V A SDN 2 BABABULO KECAMATAN PAMBOANG KABUPATEN MAJENE - Muhammad Furqan; Aliem Bahri; Anin Asnidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is a pre-experimental study that aims to determine the effectiveness ofthe use of interactive learning devices in improving the writing skills of Class Vstudents of SDN 2 Bababulo, Pamboang Pamboang District, Majene Regency, thepopulation of this study amounted to 36 students. The sample of this study wasclass V-A which amounted to 18 students. The research data were obtained andthe learning outcome test on the material of writing essays in the form of pre-testsand post-tests. The data analysis technique was descriptive statistical analysisand inferential statistics. Based on the results of the inferential analysis of the t-test design 2, the t-count value was 1.739, which was greater than the t-table11.480. It can be concluded that the use of interactive learning devices is effectivein improving the writing skills of Class V students of SDN 2 Bababulo, PamboangDistrict, Majene Regency.